Assembly and Transfer of Iron–Sulfur Clusters in the Plastid - Lu, Yan (Frontiers in Plant Science, 2018)
Iron-sulfur (Fe-S) clusters and proteins are essential to many growth and developmental processes. In plants, they exist in the plastids, mitochondria, cytosol, and nucleus. Six types of Fe-S clusters are found in the plastid: classic 2Fe-2S, NEET-type 2Fe-2S, Rieske-type 2Fe-2S, 3Fe-4S, 4Fe-4S, and siroheme 4Fe-4S. Classic, NEET-type, and Rieske-type 2Fe-2S clusters have the same 2Fe-2S core; similarly, common and siroheme 4Fe-4S clusters have the same 4Fe-4S core. Plastidial Fe-S clusters are assembled by the sulfur mobilization (SUF) pathway, which contains cysteine desulfurase (EC 2.8.1.7), sulfur transferase (EC 2.8.1.3), Fe-S scaffold complex, and Fe-S carrier proteins. The plastidial cysteine desulfurase-sulfur transferase-Fe-S-scaffold complex system is responsible for de novo assembly of all plastidial Fe-S clusters. However, different types of Fe-S clusters are transferred to recipient proteins via respective Fe-S carrier proteins. This review focuses on recent discoveries on the molecular functions of different assembly and transfer factors involved in the plastidial SUF pathway. It also discusses potential points for regulation of the SUF pathway, relationships among the plastidial, mitochondrial, and cytosolic Fe-S assembly and transfer pathways, as well as several open questions about the carrier proteins for Rieske-type 2Fe-2S, NEET-type 2Fe-2S, and 3F-4S clusters.